OC-009 Human anti-microbial vδ2+ t-cells are novel intestinal lymphocytes with functional relevance in crohn's disease. (28th May 2012) - McCarthy, N E; Hedin, C R; Vossenkämper, A; Bhattacharjee, S; Brown, S G; Sanders, T J; Giles, E M; Whelan, K; Lindsay, J O; Stagg, A J
Abstract : Introduction: Vγ9Vδ2+ "unconventional" (Vδ2) T-cells are a population of circulating anti-microbial lymphocytes found only in higher primates and whose role in human intestinal immunity is unknown. In macaques, microbe-activated Vδ2T-cells expand and accumulate in mucosal tissues, and human Vδ2T-cells can produce key mediators of intestinal inflammation such as IFNγ, TNFα and IL-17A in response to bacterial species present among the gut microbiota. We therefore hypothesised that Vδ2T-cells might contribute to the pathogenesis of Crohn's disease (CD). Methods: Disaggregated intestinal biopsies and peripheral blood were analysed by flow-cytometry in CD patients (n=22), and healthy controls (n=36). Blood and biopsy-derived cell suspensions were stimulated with microbial phosphoantigen (HDMAPP) and IL-2 in vitro to determine Vδ2T-cell phenotype, cytokine production and proliferative potential in the presence or absence of azathioprine. Results: Blood Vδ2T-cells proliferated, expressed "gut-homing" integrin β7, and produced IFNγ and TNFα upon activation with HDMAPP and IL-2 in vitro. Vδ2T-cells were also identified by confocal microscopy in both healthy and inflamed colonic lamina propria. In contrast to their blood counterparts, mucosal Vδ2T-cells expressed high levels of CD103 integrin, which is implicated in interactions with the intestinal epithelium. Although the frequency of mucosal Vδ2T-cells was low, these cells proliferated rapidly and up-regulated CD70 co-stimulatory molecule upon exposure to HDMAPP and IL-2 in vitro, consistent with responsiveness to the gut microbiota. In CD patients receiving azathioprine therapy, Vδ2T-cells were selectively lost from the blood and were markedly depleted from the lamina propria. Accordingly, physiological concentrations of azathioprine were sufficient to block HDMAPP activation of Vδ2T-cells in vitro. Conclusion: Human Vδ2T-cells primarily reside in the blood but display gut-homing potential upon microbial activation and can be detected in the intestinal mucosa. Intestinal Vδ2T-cells may contribute to local pro-inflammatory responses against the gut microbiota but are depleted by azathioprine therapy in CD. Competing interests: None declared.